CONSTRAINTS IN THE IMPLEMENTATION OF INTEGRATED INFORMATION REFERRAL SYSTEM (SISRUTE) IN EMERGENCY DEPARTMENT OF BAHTERAMAS REGIONAL GENERAL HOSPITAL - Setiawan, Harry; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
This study aims to analyze the constraints in the implementation of Integrated Information Referral System (SISRUTE) in healthcare services at Bahteramas Regional General Hospital (thereafter called RSUD Bahteramas). This study used a descriptive qualitative approach. Data were collected using in-depth interview and observation techniques. The informants in this study were selected purposively. The results of study showed that the constraints arising in the implementation of SISRUTE were caused by internal and external problems. External problems are related to the slow response of the Bahteramas Hospital’s SISRUTE, limited healthcare facilities in the emergency room, and no external socialization about the Operational Service Standards (SPO) of SISRUTE services. Meanwhile, another problem burdening the implementation of SISRUTE is related to internal conditions at RSUD Bahteramas, including computer facilities often encountering technical problems, dynamic Emergency Department (IGD) conditions with dense patient visits, no SPO available for SISRUTE services, SISRUTE not considered yet as a joint responsibility, and the application of SISRUTE on computers in the inpatient service unit. A comprehensive socialization in all First Level Healthcare Facilities (FKTP) and network hospitals is required in the attempt of uniformizing both understanding and applicable rules and the process of sending and receiving systems referring to the Director General of Healthcare Services’ Decree Number HK.02.02/D/1131/2023 about Technical Guidelines for the use of Integrated Referral Information System Applications. Keywords: constraints, implementation, system, Bahteramas Hospital